Comparative pharmacoeconomic analysis of the use of erythropoiesis-stimulating drugs for the treatment of anemia in cancer patients - I. S. Krysanov; E. V. Makarova; V. Yu. Ermakova (Медицинский совет, 2021)
Introduction. Currently, a number of pharmacoeconomic studies describing use of erythropoietin stimulating agent (ESA) in cancer patients with anemia have been published, however, most of the publications on this topic are foreign. At the same time, there are practically no studies comparing the economic efficiency of various ESA preparations with each other. Some of works by foreign colleagues reflect that the clinical efficacy of using ESA namely the degree of increase in Hb, significantly depends on the patient’s body weight: the higher the weight, the greater the dose of EPO is required for a single administration and a course of therapy.Aim. Сomparative pharmacoeconomic analysis of epoetin alfa usage for the treatment of anemia in adult cancer patients with weight 80 kg.Materials and methods. The following drugs were selected for comparative analysis: epoetin alfa, epoetin beta, darbepoetin. Clinical efficacy was assessed in terms of the rate of in Hb level increase. Pharmacoeconomic analysis was carried out using the cost-effectiveness method (CEA).Results. Тhe usage of epoetin alfa 12,000 IU for 8 weeks therapy course in cancer patients weighting over 80 kg had a better cost-effectiveness ratio compared to epoetin alfa (10,000 IU, 30,000 IU, 40,000 IU) and darbepoetin, giving way in price only to the cheapest epoetin beta which can be administered 4 injections simultaneously. Its the infringement of patients rights to avoid additional pain. Its the infringement of patients rights to avoid additional pain. At the 16th week of therapy, the usage of epoetin alfa 12,000 IU had an advantage over all ESA.Conclusions. Тhe usage of russian epoetin alfa 12,000 IU for the treatment of anemia in adult cancer patients weighing over 80 kg approximately in real clinical practice in Russian Federation is an economically justified approach to the medical care organization.